Principal's Leadership Style in Improving the Quality of Education: Voices from Madrasah Aliyah at Cilegon, Banten, Indonesia - Yusuf, Furtasan Ali; Fauzi, Anis; Suganda, Ahmad (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to (1) describe the leadership style of principal in improving the quality of education at MA Al-Inayah Cibeber and Madrasah Aliyah Al-Khairiyah Tegal Buntu Cilegon City. (2) Describe the obstacles to the leadership style of principal in improving the quality of education at Madrasah Aliyah Al-Inayah Cibeber and Madrasah Aliyah Al-Khairiyah Tegal Buntu Kota Cilegon, (3) describe the results of the leadership style of principal in improving the quality of education at MA Al-Inayah Cibeber and Madrasah Aliyah Al-Khairiyah Tegal Buntu, Cilegon City. The method in this research is using the qualitative-descriptive method. The choice of this method will make it easier to understand the data exposure that has been described because it is arranged accurately and systematically. This data collection uses observation, interviews, and documentation. The results show that the strategy adopted by the principal of MA Al-Inayah and MA Al-Khairiyah Tegal Buntu refers to the quality theory of education which includes input, process, and output. The leadership style of the head of MA Al-Inayah Cibeber, Cilegon City, turns out to lead to democratic leadership and administration. Meanwhile, the leadership style of the principal of Madrasah Aliyah Al-Khairiyah Tegal Buntu Kota Cilegon leads to a democratic leadership style. This can be seen from the interference and thoughts of the parties involved in issuing Madrasah policies.